CTLA-4 expression on CD4+ lymphocytes in patients with sepsis-associated immunosuppression and its relationship to mTOR mediated autophagic–lysosomal disorder - Cheng, Wei; Zhang, Jiahui; Li, Dongkai; Lei, Xianli; Wang, Hao; Cui, Na (Frontiers in Immunology, 2024)
Background: The aim of this study was to clarify the relationship between expression level of CTLA-4 on CD4+ T cells and sepsis-associated immunosuppression (SAI), and to elucidate the possible mechanism of mTOR pathway mediated autophagic-lysosomal disorder in regulating CTLA-4 expression. Methods: We enrolled 63 sepsis patients admitted to our ICU between January 1 and June 30, 2023. Peripheral blood mononuclear cells were isolated from the patients within 24 hours of recruitment. Expression levels of mTOR, P62, LC3II, and CTLA-4 on circulating CD4+ T lymphocytes were quantitated using flow cytometry. The association of these markers and relationship between CTLA-4 expression and the incidence of SAI and 28-day mortality were comprehensively analyzed. Results: Compared with non-immunosuppressed patients with sepsis, patients with SAI had a higher 28-day mortality rate (37.5% vs 13.0%, P=0.039) and higher CTLA-4 mean fluorescence intensity (MFI) on CD4+ T cells (328.7 versus 78.7, P<0.0001). CTLA-4 MFI on CD4+ cells was independently associated with the occurrence of SAI (95% confidence interval: 1.00–1.14, P=0.044). In patients with sepsis and SAI, non-survivors had higher CTLA-4 expression than survivors (sepsis: 427.5 versus 130.6, P=0.002; and SAI: 506.7 versus 225.2, P<0.0001). The sensitivity and specificity of CTLA-4 MFI at predicting 28-day mortality in patients with SAI was 100% and 80% respectively with the cutoff value of 328.7 and the area under the curve of 0.949. The MFI of mTOR, P62, and LC3II on CD4+ T cells were statistically higher in patients with SAI than in non-immunosuppressed patients (267.2 versus 115.9, P<0.0001; 314.8 versus 173.7, P<0.0001; and 184.7 versus 1123.5, P=0.012, respectively); P62 and LC3II were markedly higher in non-survivors than in survivors of sepsis (302.9 versus 208.9, P=0.039; and 244.3 versus 122.8, P<0.0001 respectively). The expression of CTLA-4 statistically correlated with that of LC3II in patients with sepsis, patients with SAI, and patients with SAI who did not survive (correlation coefficient: 0.69, 0.68, and 0.73, respectively, P<0.0001). Conclusions: CTLA-4 overexpression on CD4+ T cells was markedly associated with the incidence of SAI and had great relevance to 28-day mortality. mTOR pathway mediated autophagic-lysosomal disorder showed significant association with CTLA-4 expression.